Transformasi Digital Pelayanan Publik: Pembelajaran dari Implementasi Sistem OSS (Online Single Submission) - Junus Kwelju (JURNAL BADATI, 2025)
The digital era has fundamentally changed the paradigm of public services, encouraging governments to adopt digital technology to improve efficiency, transparency, and accessibility. This study analyzes the digital transformation of public services through the implementation of the Online Single Submission (OSS) system in Indonesia. Using a systematic literature review and case study approach, this research explores how the OSS, as an integrated electronic business licensing platform, has transformed the way thegovernment provides services to the public and businesses. The findings indicate that although the OSS has successfully simplified the licensing process and increased bureaucratic efficiency, its implementation still faces challenges related to digital literacy, technological infrastructure, and inter-agency coordination. This research contributes to the theoretical understanding of public sector digital transformation and provides practical recommendations for optimizing digital service systems.